Cooperation, Emergence of the Economic Agency Role of Government, and Governance - Johnson, Omotunde (IMF Working Papers; Working Paper, 1997)
This paper focuses on the emergence of the economic agency role of government and its relationship with cooperation and economic management. It distinguishes emergence under war, domination or capitulation, perfect cooperation, and strategic bargaining. Good governance is a consequence of constraints designed by principals with the incentive and ability to do so. The incentives are related inversely to the expected relative frequency of controlling government and directly to the expected relative share of costs of poor agency. The ability is directly related to bargaining power in determining the agency role. There are implications for the evolution of cooperation in the society and for macroeconomic performance.